Using a well-to-well interplay during the CO2 huff-n-puff process for enhanced oil recovery in an inclined oil reservoir: Experiments, simulations, and pilot tests - Hao, Hongda; Hou, Jirui; Qu, Ming; Guo, Wenmin; Deng, Song; Liu, Huaizhu (Frontiers in Energy Research, 2023)
A well-to-well interplay of CO2 huff-n-puff is proposed as a novel gas injection strategy for displacing interwell-remaining oil in a well pair in an inclined oil reservoir. The well-to-well interplay mechanisms for enhanced oil recovery (EOR) are first studied in the laboratory using a three-dimensional (3D) physical model. Different CO2 injection schemes are designed according to different well locations, and the production performance including oil, water, and gas rates is used for the EOR evaluation. A sensitivity analysis of the well-to-well interplay is then studied using a numerical model, and geological, developmental and fluidic factors are considered in the simulations. The experimental results show that, when CO2 is injected into a lower well, a higher well always benefits with an oil increment. Under the effects of gravity segregation and edge-water driving, the injected CO2 at the lower position can move upward to a higher position, where a large proportion of crude oil remains between wells after natural edge-water flooding. Oil recovery from the well-to-well interplay is 2.30% higher than conventional CO2 huff-n-puff in the laboratory. Numerical results show that CO2 injection mass, stratigraphic dip, horizontal permeability, and interwell spacing are the factors that most influence the well-to-well interplay; an application criterion for the well-to-well interplay is then proposed based on the simulations. Pilot tests using the well-to-well interplay of CO2 huff-n-puff have been widely applied in C2-1 Block, Jidong Oilfield, China, since 2010. A total of 2.27 × 104 m3 crude oil was recovered to the end of 2018, and the oil/CO2 exchange ratio was as high as 3.92. The well-to-well interplay not only effectively extracted the interwell-remaining oil but also achieved higher CO2 utilization efficiency. The findings of this study can lead to a better understanding of the EOR mechanisms used in the well-to-well interplay during the CO2 huff-n-puff process in an inclined oil reservoir.